Checkpoint inhibitors in the treatment of brain metastases of non-small-cell lung cancer and melanoma. (May 2017) - Kourie, Hampig Raphael; Kanaan, Hassan; Awada, Gil; Awada, Ahmad Hussein
Brain metastases (BMs) are representing a new challenge for the oncologist; their incidence is increasing due to the better overall survival and systemic disease control in many malignancies, consequent to new potent cytotoxic and targeted therapies. In the era of immunotherapies, checkpoint inhibitors are representing a new therapeutic option in different solid tumors and settings; preliminary results showed potential activity of these agents in patients with BM, when administered as single agent or in combination with radiation therapy. After presenting the arguments in favor of this new strategy, we reported the preliminary results of the trials evaluating these agents in BM, we described the ongoing trials and we discussed the potential role of these agents in the BM treatment.